Alleviation of soil acidity using basalt and bio-fertilizer for rice cultivation - Oslan, Nur Lyana Farhan; Jusop, Shamshuddin; Othman, Radziah (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
This paper presents on how to overcome soil acidity in rice cultivation area. Yields of paddy become unproductive when planted at soil which low in pH < 3. The average yields less than 2 t/ha/season, where far low from the national average. A study was conducted with the objective of increasing rice yields on acidic soils condition. The acid sulfate soil was treated using basalt and biofertilizer at specific rate. The pH of the soils increase from 3.93 (1st season) to 4.23 (2nd season) when soil was treated with combination of 4 t/ha basalt and 2 t/ha bio-fertilizer. The yield from this treatment is 60.13 g/pot which higher compared to the control (24.10 g/pot). The applications of these 2 amendments at the appropriate rate are able to increase the paddy yields and also improve the soil quality.